MHD‐Test Particles Simulations of Moderate CME and CIR‐Driven Geomagnetic Storms at Solar Minimum - Mary K. Hudson; Scot R. Elkington; Zhao Li; Maulik Patel; Kevin Pham; Kareem Sorathia; Alex Boyd; Allison Jaynes; Alexis Leali (Space Weather)
Abstract As part of the Whole Heliosphere and Planetary Interactions initiative, contrasting drivers of radiation belt electron response at solar minimum have been investigated with MHD‐test particle simulations for the May 13–14, 2019 Coronal Mass Ejection (CME)‐shock event and the August 30–September 3, 2019 high speed solar wind interval. Both solar wind drivers produced moderate geomagnetic storms characterized by a minimum Dst = −65 nT and −52 nT, respectively, with the August ‐ September event accompanied by prolonged substorm activity. The latter, with characteristic features of a Corotating Interaction Region (CIR)‐driven storm, produced the hardest relativistic electron spectrum observed by Van Allen Probes during the last two years of the mission, ending in October 2019. MHD simulations were performed using both the Lyon‐Fedder‐Mobarry global MHD code and recently developed GAMERA model coupled to the Rice Convection Model, run with measured L1 solar wind input for both events studied, and coupled with test particle simulations, including an initial trapped and injected population. Initial electron Phase Space Density (PSD) profiles used measurements from the Relativistic Electron Proton Telescope and MagEIS energetic particle instruments on Van Allen Probes for test particle weighting and updating of the injected population at apogee. Results were compared directly with measurements and found to reproduce magnetopause loss for the CME‐shock event and increased PSD for the CIR event. The two classes of events are contrasted for their impact on outer zone relativistic electrons near the end of Solar Cycle 24.